Research plans in Europe for radiation health hazard assessment in exploratory space missions. (May 2019) - Walsh, L.; Schneider, U.; Fogtman, A.; Kausch, C.; McKenna-Lawlor, S.; Narici, L.; Ngo-Anh, J.; Reitz, G.; Sabatier, L.; Santin, G.; Sihver, L.; Straube, U.; et al.
Abstract: The European Space Agency (ESA) is currently expanding its efforts in identifying requirements and promoting research towards optimizing radiation protection of astronauts. Space agencies use common limits for tissue (deterministic) effects on the International Space Station. However, the agencies have in place different career radiation exposure limits (for stochastic effects) for astronauts in low-Earth orbit missions. Moreover, no specific limits for interplanetary missions are issued. Harmonization of risk models and dose limits for exploratory-class missions are now operational priorities, in view of the short-term plans for international exploratory-class human missions. The purpose of this paper is to report on the activity of the ESA Topical Team on space radiation research, whose task was to identify the most pertinent research requirements for improved space radiation protection and to develop a European space radiation risk model, to contribute to the efforts to reach international consensus on dose limits for deep space. The Topical Team recommended ESA to promote the development of a space radiation risk model based on European-specific expertise in: transport codes, radiobiological modelling, risk assessment, and uncertainty analysis. The model should provide cancer and non-cancer radiation risks for crews implementing exploratory missions. ESA should then support the International Commission on Radiological Protection to harmonize international models and dose limits in deep space, and guarantee continuous support in Europe for accelerator-based research configured to improve the models and develop risk mitigation strategies.